2023
DOI: 10.1097/md.0000000000032719
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of mindfulness on demoralization syndrome and quality of life of thyroid cancer patients: A correlational study

Abstract: Demoralization syndrome is prevalence among cancer patients in China. However, little research has examined how demoralization syndrome is associated with quality of life (QOL). The aims of this study were to investigate the relationship between mindfulness state, demoralization syndrome and QOL of thyroid cancer patients, and explore the mediating effect of mindfulness on demoralization syndrome and QOL. A correlational cross-sectional study was performed using an online questionnaire. The study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Therefore, teaching self-expression and role-playing skills, together with mindfulness exercises as coping tools, can increase patients' ability to act, help them build self-con dence, and prepare them for future action, which in turn can increase their hope (Pouyanfard et al, 2020). Also, when the patients can observe their inner feelings, they can promote conscious action, consciously regulate bad feelings, and have better psychological management of symptoms to reduce the occurrence of demoralization syndrome (YuYu et al, 2023). Also, the present study showed that mindfulness-integrated cognitive behavior therapy improved sexual performance in patients.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, teaching self-expression and role-playing skills, together with mindfulness exercises as coping tools, can increase patients' ability to act, help them build self-con dence, and prepare them for future action, which in turn can increase their hope (Pouyanfard et al, 2020). Also, when the patients can observe their inner feelings, they can promote conscious action, consciously regulate bad feelings, and have better psychological management of symptoms to reduce the occurrence of demoralization syndrome (YuYu et al, 2023). Also, the present study showed that mindfulness-integrated cognitive behavior therapy improved sexual performance in patients.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Therefore, patients with a high level of mindfulness can treat their illness and life with a peaceful and accepting attitude. Also, mindfulness helps patients to improve their emotional stability and ability to cope with stress to achieve good psychological adjustment and personal growth (YuYu et al, 2023). Therefore, based on the effectiveness of MICBT treatment on the symptoms of women with breast cancer, it is suggested that psychologists and counselors use this treatment as an adjunctive treatment to reduce demoralization and body image and improve sexual performance in women with breast cancer.…”
Section: Ethical Considerationsmentioning
confidence: 99%